Suprapapillary needle puncture for common bile duct access: laboratory profile - Artifon,Everson L. A. (2006)
BACKGROUD: Biliary cannulation to perform endoscopic retrograde cholangiopancreatography may be difficult due to technical reasons and often is necessary to perform papillotomy, where complications as pancreatitis and perforation may occur AIM: To show minimal complications by a new model of biliary access by means of the suprapapillary needle puncture and its laboratory profile. PATIENTS AND METHODS: After the approval of the protocol by the Scientific Ethics Committee of the institution a free and informed consent was signed by all patients participating in the study. From July 2003 to August 2004, fulfilling the inclusion and exclusion criteria, 30 patients were selected for endoscopic retrograde cholangiopancreatography, using the suprapapillary puncture technique. All patients remained hospitalized, fasting and with basal hydroelectrolytic replacement, were clinically followed up and samples for the determination of serum amylase, lipase and C-RP (C-reactive protein) were collected before and 4 h, 12 h and 24 h after the procedure and reevaluated 60 days after the procedure. Laboratory parameters were submitted to statistical study using analysis of variance for repeated measurements. Multiple comparisons were made based on Wald's statistics RESULTS: The technique was successful in 93.4% (28/30) of the patients. No statistically significant difference regarding to the laboratory profile were observed. Complications related to the technique of papillary puncture occurred in 1/28 patients by not using the guide wire and in 1/28 where mild hemorrhage after dilation of the papillary fistula occurred. Regarding complications related to therapeutic procedures, there were 2/28 retroduodenal perforations, with one (1/30) following unsuccessful puncture and another due to the passage of Dormia's basket through the dilated fistula path. All patients submitted to diagnostic puncture and evaluated 60 days after the procedure presented with the major duodenal papilla of normal aspect. The patients with dilation of the suprapapillary fistula showed the fistula continuing to drain clear bile CONCLUSION: Suprapapillary puncture allows investigative and therapeutic procedures without significant increases in amylase, lipase and C-RP. Patients submitted to diagnostic puncture present complete recovery of the papilla, while dilation of the fistula maintains it pervious later on, but without complications.